THE ISLAMIZATION OF THE MALAY SULTANATE: TRACING THE HISTORICAL ROOTS OF ISLAMIC INFLUENCE IN MALAYSIA - S, Samsidar; S., Syamsuduha; Pababbari, Musafir; Shafiq, Kamaruzzaman (Institut Agama Islam Negeri Bone, 2024)
The development of Islam in Malaysia is an interesting phenomenon to study. As a country with a majority Muslim population, Malaysia has its own dynamics in the process of Islamization and the evolution of Islamic thought in this region. The process of Islamization in Malaysia cannot be separated from the central role of the Malay sultanates, which helped spread and develop the teachings of Islam since the 13th century. Through political power and trade relations, Islam was deeply rooted in the culture and identity of the Malay people. In its development, Islam in Malaysia underwent various transformations. From traditionalism to modern revivalism, Islamic thought and movements in the country continue to evolve in line with political, social and cultural dynamics. The Islamic revival that occurred since the 1970s also colored the religious landscape in Malaysia. The issue of the relationship between Islam and politics has also become one of the main focuses in the development of Islam in Malaysia. The interaction between religion and the state, as well as its implications for people's religious life, is a hot topic that continues to be debated. In addition, Malaysia is also known as a country with religious and cultural diversity. In this context, maintaining inter-religious harmony is a challenge for the Muslim community in Malaysia. The development of Islam in Malaysia also includes the aspect of education, where traditional Islamic education systems such as Islamic boarding schools are developing parallel to the establishment of leading Islamic universities. This dynamic has helped shape the character of Islamic thought and spirituality in Malaysian society.